2020
DOI: 10.36834/cmej.68376
|View full text |Cite
|
Sign up to set email alerts
|

Exercise is medicine Canada workshop training improves physical activity practices of physicians across Canada, independent of initial confidence level

Abstract: Background: Educational workshops help physicians (MDs) include physical activity and exercise (PAE) content in more patient appointments. It is unclear if MDs with varying degrees of self-confidence discussing PAE with their patients equally benefit from such training. We evaluated whether MDs’ initial self-confidence affects the impact of an educational PAE workshop. Methods: MDs (n = 63) across Canada completed self-reflection questionnaires initially and 3-months following a PAE workshop. MDs were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
(52 reference statements)
0
9
0
3
Order By: Relevance
“…Studies that have assessed whether this initiative does indeed lead to increased inclusion of physical activity in clinical interactions have shown positive results. For example, O'Brien et al (11) tested the effect of educational exercise workshops with physicians with varying degrees of physical activity competence and confidence to prescribe exercise. The workshop included training on assessing physical activity vital signs, communication strategies for discussing physical activity with patients, and referrals to resources and personal (11).…”
Section: Exercise Is Medicine In Pregnancymentioning
confidence: 99%
See 2 more Smart Citations
“…Studies that have assessed whether this initiative does indeed lead to increased inclusion of physical activity in clinical interactions have shown positive results. For example, O'Brien et al (11) tested the effect of educational exercise workshops with physicians with varying degrees of physical activity competence and confidence to prescribe exercise. The workshop included training on assessing physical activity vital signs, communication strategies for discussing physical activity with patients, and referrals to resources and personal (11).…”
Section: Exercise Is Medicine In Pregnancymentioning
confidence: 99%
“…For example, O'Brien et al (11) tested the effect of educational exercise workshops with physicians with varying degrees of physical activity competence and confidence to prescribe exercise. The workshop included training on assessing physical activity vital signs, communication strategies for discussing physical activity with patients, and referrals to resources and personal (11). Findings showed that confidence for integrating physical activity into their practice significantly increased, and at the 3-month follow-up, the majority of participants reported a significant increase in writing and discussing physical activity prescriptions and referrals (11).…”
Section: Exercise Is Medicine In Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Our results indicate that interventions that use a dual-education model (i.e., lecture-based and practical components) that incorporates targeted learning outcomes are the most effective for increasing PA counseling and exercise prescription rates. These targeted learning outcomes may include educating physicians on accredited PA guidelines (13,16), resources to use and/or implement in their practice (28,35), or problem-solving strategies (11,20,28). Theoretical interventions (i.e., interventions in which lectures were the sole form of delivery) were also effective in increasing physician PA counseling and prescription practices, although a practical component as an extension of the theoretical training could further improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Some interventions included supplemental tools, such as exercise prescription pads (23,30), or summary packages of the topics discussed during the intervention (18,22,27). Outcomes were assessed using surveys (i.e., physician-evaluated changes in outcomes) (16,32), interviews with health care providers (21,30), or patient reports (i.e., patient-evaluated changes in outcomes) (18,22,25,27). Additional details of the educational components of each interventional study reviewed are presented in Supplemental Content 3 (table, http://links.lww.com/ TJACSM/A237).…”
Section: Study Characteristicsmentioning
confidence: 99%